Faktor-Faktor yang Memengaruhi Adopsi Teknologi Pembayaran Kode QR pada Pelaku UMKM - Dzaki Hanif; Diena Noviarini; Ringga Sentagi Asa (INDO PUBLISHING, 2026)
This study aims to analyze the factors influencing Behavioral Intention to Use QRIS among culinary micro, small, and medium enterprises (MSMEs) in DKI Jakarta using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model extended with Perceived Security and Perceived Trust variables. This study employed a quantitative approach with a survey method involving 214 MSME respondents who have used QRIS. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that Performance Expectancy, Effort Expectancy, Price Value, Perceived Security, and Perceived Trust have a positive and significant effect on Behavioral Intention to Use QRIS, with Perceived Trust being the most influential factor. Meanwhile, Social Influence was found to have no significant effect. The R² value of 0.578 indicates that the model explains 57.8% of the variation in behavioral intention to use QRIS. These findings suggest that increasing QRIS adoption among MSMEs should be supported by providing beneficial and easy-to-use services, costs commensurate with benefits, robust security systems, and efforts to build MSME owners' trust in QRIS as a digital payment method. This study contributes to the development of UTAUT2 literature by extending the model in the context of digital payment adoption in the MSME sector.